Determinants of job pursuit intention among private university students in Malaysia - Chong, Hor En; Lee, Chuan Ann; Law, Yuki (2025)
In today's competitive job market, organizations have significant challenges in attracting and maintaining skilled employees, particularly in developing countries such as Malaysia. Malaysia faces substantial workforce issues, such as brain drain and unemployment. This study examines the determinants that influence job pursuit intention among private university students in Malaysia, with focus on salary, quality of work life and corporate social responsibility. A quantitative approach was used, with data collected from 395 respondents at three private universities in Perak through a structured questionnaire. The data have been assessed by descriptive statistics, reliability tests, and multiple linear regression. The results show that all determinants, salary, quality of work life and corporate social responsibility have significant influence job pursuit intention with corporate social responsibility as the most significant determinant ((β = 0.365, p < 0.001), followed by quality of work life (β = 0.341, p < 0.001) and salary (β = 0.120, p = 0.013). The findings indicate that, while salary remains a critical criterion, students prefer organizations with strong ethical standards environmental sustainability as well as employee well-being. The study also highlights the changing preferences of generation Z, which prioritize meaningful work and work-life balance instead of competitive salary. This research has crucial implications for organizations seeking to attract and retain young talent. Employers are encouraged to boost their corporate social responsibility initiatives, promote better working environment and provide flexible work arrangements to meet the expectations of future employees. Meanwhile, universities can use these findings to better prepare students for the job market by developing partnership with socially responsible organizations.